Dynamics of double plume emissions in TEA-CO2 laser ablation of graphite - Siew, W.O.; Tou, T.Y.; Yap, S.S.; Wong, K.H.; Chin, Oi Hoong (Institute of Electrical and Electronics Engineers (IEEE), 2003)
Streak photography of TEA-CO2 laser ablation of graphite in helium (He) and argon (Ar) background gases shows two luminous fronts, that are spatially and temporally separated, lifting off the graphite target. The velocity profile of the second front appears to follow closely that of the first luminous front. The second front is absent if the laser-supported absorption wave sets in when the background gas pressure is increased to 50-mbar Ar. The optical emission spectroscopy display many of triply, doubly, and singly ionized carbon species in the expanding plume at < 0.3 mbar He, while the excited and singly ionized helium species are found in (1-30) mbar He which coincides with streak observations of strong luminous fronts. Computer simulations of the propagation trajectories of luminous fronts are carried out using the blast-wave, drag, and the snowplow models.